Oxford mathemtics for Queensland : - Wasley, Barbara (Oxford University Press, 1996)
This book is the second in a series of three textbooks written by experienced Queensland teachers for Queensland students year 8.9 and 10. This textbook series provides comprehensive coverage of the 1-10 Mathematics Syllabus.